2008
DOI: 10.1634/stemcells.2008-0353
|View full text |Cite|
|
Sign up to set email alerts
|

Human T-Cell Lymphotropic Virus Type 1 Infection of CD34+ Hematopoietic Progenitor Cells Induces Cell Cycle Arrest by Modulation of p21cip1/waf1 and Survivin

Abstract: STEM CELLS 2008;26: 3047-3058 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…HTLV-1 infection of key target HP/HSCs in infants infected at birth has been proposed to be a predisposing factor in the development of leukemia/lymphoma. 14,20,23,29,30 Allogeneic BM transplantation involving HTLV-1-infected stem cell donors has been associated with virus transmission, 31 implicating HP/HSCs as harboring viral infection. Reconstitution of hematopoiesis in NOD/SCID mice with the use of HTLV-1-infected or Tax1-transduced human CD34 ϩ HP/HSCs reproducibly recapitulates mature T-cell lymphomas with characteristic genetic, immunologic, histologic, pathologic, and clinical features of ATLL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HTLV-1 infection of key target HP/HSCs in infants infected at birth has been proposed to be a predisposing factor in the development of leukemia/lymphoma. 14,20,23,29,30 Allogeneic BM transplantation involving HTLV-1-infected stem cell donors has been associated with virus transmission, 31 implicating HP/HSCs as harboring viral infection. Reconstitution of hematopoiesis in NOD/SCID mice with the use of HTLV-1-infected or Tax1-transduced human CD34 ϩ HP/HSCs reproducibly recapitulates mature T-cell lymphomas with characteristic genetic, immunologic, histologic, pathologic, and clinical features of ATLL.…”
Section: Discussionmentioning
confidence: 99%
“…20,27 In brief, cells from various murine organs were resuspended in phosphatebuffered saline with 2% human serum (Jackson ImmunoResearch Laboratories) and 2% mouse serum (Invitrogen). For surface antigen detection, the cells were stained with a combination of 5 L each of murine anti-human CD4-fluorescein isothiocyanate, CD3-PE, CD8-Pe-CY7, CD19-APC-CY7, CD45-APC, CD25-APC, CD34-PE,CD38-APC, and CD14-PE-Cy7 (BD Biosciences) and rabbit anti-mouse CD45-peridinin chlorophyll protein complex (BD Biosciences) antibody at 4°C for 20 minutes.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…31 HTLV-1 or HHV8 infects CD34 + HSCs. 32 Primitive HSCs are resistant to HIV infection, although these cells become increasingly susceptible once they begin to differentiate into committed HSCs. 33 EBV might not infect BM, but infect peripheral or thymic CD34 + CD4 − CD8 − T-cell precursors (DN1/2) prior to the differentiation into ␣␤T-cells and ␥␦T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrate that HBZ, and to a lesser extent APH-2 significantly upregulates survivin expression. To our knowledge this is the first report showing that APH-2 can regulate survivin, though both Tax1 (Kawakami et al, 2005; Banerjee et al, 2008), and recently, HBZ (Mitobe et al, 2015) have been demonstrated to modulate survivin. As elevated levels of survivin are linked to the pathogenesis of HTLV-1, our study coupled with the work of Mitobe et al Mitobe et al, (2015) strongly supports a role for HBZ in survivin regulation.…”
Section: Discussionmentioning
confidence: 84%